Hierarchical Spin‐Crossover Cooperativity in Hybrid 1D Chains of FeII‐1, 2, 4‐Triazole Trimers Linked by [Au(CN)2]− Bridges. Issue 16 (17th February 2021) - Ezzedinloo, Lida; Zenere, Katrina A.; Xie, Zixi; Ahmed, Manan; Scottwell, SynØve; Bhadbhade, Mohan; Brand, Helen E. A.; Clegg, Jack K.; Hua, Carol; Sciortino, Natasha F.; Parker, Lachlan C.; Powell, Benjamin J.; et al.
Abstract: Foremost, practical applications of spin‐crossover (SCO) materials require control of the nature of the spin‐state coupling. In existing SCO materials, there is a single, well‐defined dimensionality relevant to the switching behavior. A new material, consisting of 1, 2, 4‐triazole‐based trimers coordinated into 1D chains by [Au(CN)2 ] − and spaced by anions and exchangeable guests, underwent SCO defined by elastic coupling across multiple dimensional hierarchies. Detailed structural, vibrational, and theoretical studies conclusively confirmed that intra‐trimer coupling was an order of magnitude greater than the intramolecular coupling, which was an order of magnitude greater than intermolecular coupling. As such, a clear hierarchy on the nature of elastic coupling in SCO materials was ascertained for the first time, which is a necessary step for the technological development of molecular switching materials. Abstract : Hierarchical cooperativity : Crucial information on the nature, magnitude, and dimensional hierarchy of elastic coupling in spin‐crossover systems is achieved in a family of materials consisting of trimers linked into coordination chains and spaced by anions and exchangeable guests.